Glasba, politika, afekt Novo življenje partizanskih pesmi v Sloveniji - Hofman, Ana (Kulturni spomin, 2015)
The book Glasba, politika, afekt: novo življenje partizanskih pesmi v Sloveniji ('Music, Politics, Affect: New Lives of Partisan Songs in Slovenia') explores the potentialities of music in imagining alternatives and establishing alliances, which introduce new senses of belonging and solidarity in global neoliberal capitalism. It examines the reactualization of partisan songs in post-Yugoslav Slovenia with an emphasis on the collective spirit, its rebelliousness and emancipatory potential. In researching the "new lives" of partisan songs, the book focuses on the self-organized female choir Kombinat, an emblematic example of thinking about the partisan art in Slovenia today. Just a part of Kombinat repertoire, partisan songs are discursively, sonically, spatially, ideologically and symbolically reloaded, challenging thus the various boundaries in thinking about this legacy in Slovenian context. Using theoretical framework of affect theory, and particularly theories of music materialism and sonic affect, the book provides an alternative perspective to our understanding of political capacity of music. It addresses four main issues: the role of music and sound in political mobilization and participation, the potentials of musical alliances and musical self-organization and self-education, referencing musical past as a way of political engagement, and finally, revitalization and reactualization of socialist ideas and values in the current moment of global transition.